"Christ transforming culture"? Nagedink oor die aard van die gereformeerde geloof - D. Smit (Acta Theologica)
The essay pays tribute to the honoree by reflecting on the nature of the Reformed faith and tradition, in which he was called to play a leading role during challenging times. It takes its departure in H. Richard Niebuhr’s well-known claim that the Reformed faith represents a form of “Christ transforming culture” Christianity, implying both that the Reformed faith positively affirms reality and life and that Reformed faith continuously strives for transformation and renewal of reality and life. The essay demonstrates how this twofold emphasis, of affirmation and critical renewal at the same time, is rooted in the heart of the Reformed vision itself, which is described as “a way of being the Christian community in the world, before God”. Four aspects of this description are consecutively highlighted, namely “the Christian community” (the first section), “before God” (the second section), “a way of being” (the third section) and “in the world” (the fourth section). In a concluding section the essay argues that four popular forms of criticism of the Reformed faith, widespread in South Africa today, are therefore directed at caricatures and betrayals of the Reformed tradition.